Nilai Pendidikan Karakter pada Tokoh Utama Novel Merakit Kapal Karya Shion Miura dan Novel Padang Bulan Karya Andrea Hirata serta Relevansinya terhadap Pembelajaran Sastra di SMA - Putri, Adzkiya; Warni, Warni; Rustam, Rustam (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
One type of self-potential creation and changes in students' mentality and behavior must be made possible through an instructive cycle. Character education is a course of doing students' requests to become people of truly good character regarding heart, mind, body, feelings, and goals. The reason for this study is to work on the nature of execution and learning outcomes that lead to the achievement of student character development through learning to write Indonesian. This kind of examination differs subjectively, by describing, recording, endlessly interpreting how the positive side of character education is depicted in the basic characters in Shion Miura's shrewd Merakit Kapal and Andrea Hirata's original Padang Bulan novel. The research method uses a qualitative descriptive method by examining the educational value documents of the main characters in the novel Merakit Kapal by Shion Miura and the novel Padang Bulan by Andrea Hirata and examines their relevance to literary learning in high school. The value of character education depicted in the main character of the novel Merakit Kapal combines the strengths of the original characters in the form of being trained, brave, intelligent, caring, independent, shy, gentle, beautiful, focused, and socially caring. Meanwhile, the value of character education depicted in the main character Padang Bulan by Andrea Hirata includes personal strengths that are firm, honest, brave, fair, shrewd, obligation, autonomy, covering disgrace, majesty, love for the homeland, hard worker, and social considerations.